MUSCLES AND MALOCCLUSION – A REVIEW - M, SHIJEE; ARANGANNAL, PONNUDURAI; J, JEEVARANTHAN; VINODHINI, JANANI; MADHUMITHA; CHELLAMAL, RAMYA; G R, ISHWARYA DHEVI; BASSI, MAYHAR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Although bone is the hardest tissue in the body, it is responsive to change when there is alteration in environmental balance. The major factor in this environmental balance is the musculature. The integrity of dental arches and relations of the teeth to each other within each arch and with opposing members are modified by stabilizing and active functional forces of orofacial muscles and the tongue. Aberrations of muscle function seen in oral habits such as thumb and digit sucking, tongue thrusting, mouth breathing, lip sucking and nail biting can and do produce marked malocclusion. Treating malocclusion is gaining more attention among patients in the current decades due to the raising esthetic concern. Also, today’s parents are much bothered on the appealing appearance of their children. Comprehensive orthodontic management should not only correct the arch form and teeth, but also involve identification of the possible etiologic factors and an attempt to eliminate the same. So, it is very important to have a knowledge regarding the effect of orofacial muscles and tongue on malocclusion which is emphasized in this presentation